2020
DOI: 10.1155/2020/6207297
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle as Risk Factor for Infectious Causes of Death in Young Dogs: A Retrospective Study in Southern Italy (2015–2017)

Abstract: Infectious diseases are a common cause of death in young dogs. Several factors are thought to predispose young dogs to microbiological infections. Identifying the cause of death is often a challenge, and broad diagnostic analysis is often needed. Here, we aimed to determine the infectious causes of death in young dogs aged up to 1 year, examining how it relates to age (under and over 6 months), lifestyle (owned versus ownerless), breed (purebred and crossbreed), and gender. A retrospective study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(75 reference statements)
1
10
1
Order By: Relevance
“…Although in a few dogs (id. 6, 7, 11, 21, 22, 19) co-infections with other viruses (CCoV and CAdV-1) were assessed, the results confirm that CPV infection remained the main cause of viral enteritis and acute hemorrhagic diarrhea syndrome (AHDS) in young dogs [ 33 , 34 ]. Therefore, a diagnostic panel for the main pathogenic bacteria and multiple viral agents should be considered in dogs with suspected infectious gastrointestinal disease [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although in a few dogs (id. 6, 7, 11, 21, 22, 19) co-infections with other viruses (CCoV and CAdV-1) were assessed, the results confirm that CPV infection remained the main cause of viral enteritis and acute hemorrhagic diarrhea syndrome (AHDS) in young dogs [ 33 , 34 ]. Therefore, a diagnostic panel for the main pathogenic bacteria and multiple viral agents should be considered in dogs with suspected infectious gastrointestinal disease [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 76%
“…Despite the fact that vaccination has considerably reduced the occurrence, canine parvovirus infection remains a global threat to domestic and wild carnivores. Until now, studies have been focused on CPV infection and global spread, with limited studies on co-infections with bacteria or other viruses [ 17 , 20 , 33 , 34 ]. In this study, samples collected from dog carcasses with CPV infection were analyzed to evaluate the impact of the bacterial species, their susceptibility to antibiotics, and their multidrug resistance, along with other viral co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Viral enteritis is a major threat to pet dogs that can lead to life-threating illness. Canine parvovirus (CPV-2), canine distemper virus (CDV), canine coronavirus (CCoV) and canine adenovirus (CAV) are the main pathogens that cause canine viral enteritis ( Cardillo et al, 2020 ; Deng et al, 2018 ). In this study, Cachavirus, belonging to ChPV, was reported for the first time in diarrheic dogs in China; however, statistical analysis showed no association between the presence of the virus and clinical signs ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial species is uncommonly associated with life-threatening infections. An Italian retrospective study investigating infectious causes of death in young dogs did not detect S. pseudintermedius among the most common bacterial species (Cardillo et al, 2020). S. pseudintermedius is usually isolated from skin infections and otitis externa, which are usually mild to moderate, although sporadic cases of rapidly progressive and rare conditions of fatal necrotising fasciitis have been reported in dogs (Weese et al, 2009).…”
Section: The Availability Of Effective Prevention or Medical Treatmen...mentioning
confidence: 99%